Current Situation of Building and Development of Ethnic Minority Staff in Vietnam - Tran Hoang Khai (Journal La Sociale, 2021)
As a multi-ethnic country, the Party and the State of Vietnam have always determined that ethnic affairs and national solidarity have a huge significant position. Building a contingent of ethnic minority staff in the political system remains one of the solutions to realize equality and solidarity among ethnic groups. The recent building of ethnic minority staff has been paid special attention and achieved certain remarkable results. The quality of ethnic minority staff has been increasingly improved. This importantly contributes to the socio-economic development of Vietnam in the upcoming years.